2021
DOI: 10.1037/spq0000426
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the initial impact of COVID-19 on burden and psychological distress among family caregivers of children with and without developmental disabilities.

Abstract: The current COVID-19 pandemic is presenting challenges for families (Cluver et al., 2020), which may be exacerbated for caregivers of children with developmental disabilities (DDs; Center on the Developing Child, 2020). The purpose of this study was to explore caregiver burden and psychological distress among caregivers of children with DD as compared to caregivers of typically developing children across the United States as a result of COVID-19. Between 2 weeks and 1 month following COVID-19-related school cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 26 publications
(41 reference statements)
4
25
0
Order By: Relevance
“…Second, this study is exclusively focused on relatives of people with intellectual and developmental disability, and their situation cannot be compared with that of other families who did not live with people with disabilities during lockdown. Studies such as that by Chafouleas and Iovino (2021) and Willner et al, (2020) note that, although many families with children without disabilities have experienced difficulties, these have been greater for those who have a child with intellectual and developmental disability (Willner et al, 2020). whether support and services will continue as they used to be so far, and about the impact of lockdown and COVID-19 on the health of the person with disability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, this study is exclusively focused on relatives of people with intellectual and developmental disability, and their situation cannot be compared with that of other families who did not live with people with disabilities during lockdown. Studies such as that by Chafouleas and Iovino (2021) and Willner et al, (2020) note that, although many families with children without disabilities have experienced difficulties, these have been greater for those who have a child with intellectual and developmental disability (Willner et al, 2020). whether support and services will continue as they used to be so far, and about the impact of lockdown and COVID-19 on the health of the person with disability.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, except for the studies by Redquest et al (2021), whose specific target are the siblings of adults, and Willner et al (2020), which includes both adult and under‐age populations, they all focus on child‐youth population. Moreover, only six studies address the particular challenges that the family members of people with more extensive support needs might have faced (Bentenuto et al, 2021; Canning & Robinson, 2021; Chafouleas & Iovino, 2021; Kim et al, 2021; Paulauskaite et al, 2021; Willner et al, 2020), and most of them, except for the paper by Willner et al (2020), that addresses diverse effects of the COVID‐19 pandemic on relatives of both adults and children, focus exclusively on underage population with behavioural problems or autism spectrum disorder, placing specific emphasis on analysing the impact of the closure of educational facilities. It is, therefore, necessary to delve into the experiences of relatives of people with intellectual and developmental disabilities, both adult and underage, during the health emergency and lockdown period, while also analysing whether those who have supported people with more extensive needs have been exposed to situations of particular vulnerability or stress.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the pandemic, caregivers of children with ASD further reported higher levels of burden, stress, anxiety, and depression compared with caregivers of typically developing children. 15 Parents of children with special needs are also less likely to be equipped to continue the child's learning remotely, further exacerbating their educational disadvantage. 16 Children with IDD are at a greater risk for mental health symptoms than their neurotypical peers.…”
Section: Indirect Impact Of the Covid-19 Pandemic On Children With Idd And Cmcmentioning
confidence: 99%
“…We are just now beginning to assess the acute impact on children, families, providers, and health care systems. Observational studies have reported worsening in ADHD (Zhang et al., 2020 ), more internalizing symptoms, as well as increases in negative health behavior such as increased screen time, less physical activity, and irregular sleep habits (Chafouleas & Iovino, 2021 ; Sibley et al., 2021 ). Not surprisingly, risk factors such as less sleep and more screen time are correlated with depressive symptoms (Chafouleas & Iovino, 2021 , p. 4; Swansburg, 2021, p. 5).…”
mentioning
confidence: 99%